Large-scale preparation method and application of monatomic ammonia decomposition catalyst
Through mechanical ball milling, hexagonal boron nitride and cerium acetylacetone are mixed with the acetylacetone salt of the active metal, and large-scale preparation of a single atomic ammonia decomposition catalyst is achieved, solving the problems of high preparation costs and environmental pollution in the prior art, and achieving efficient and low-cost catalyst preparation.
Patent Information
- Application Number
- CN202411927971.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-25
AI Technical Summary
It is difficult to prepare efficient and low-temperature single-atomic ammonia decomposition catalysts on a large scale, and commonly used liquid phase synthesis methods have problems of high cost and environmental pollution.
The mixed material of the layered material hexagonal boron nitride and cerium acetylacetone is used as the precursor of the composite support, and mixed with the acetylacetone salt of the active metal for ball milling, followed by heat treatment to achieve the atomic dispersion load of the active metal.
Large-scale preparation of single-atom ammonia decomposition catalysts is realized, which improves the activity and atomic utilization of the catalysts, reduces costs, and is simple in process and environmentally friendly.
Smart Images

Figure CN119680607A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of hydrogen production, and in particular to a large-scale preparation method and application of a single-atom ammonia decomposition catalyst. The method is a method for preparing an ammonia decomposition hydrogen production catalyst by mechanical ball milling. Background Art
[0002] Among secondary energy carriers, hydrogen is considered to be an ideal substitute for fossil fuels due to its abundant sources, high combustion calorific value, and zero carbon emissions. However, due to the low volume density, low lower explosion limit, and flammability of hydrogen, there are problems such as high cost and low safety in transportation and storage. Researchers have explored different methods to solve this problem. Among them, using hydrogen-containing compounds as hydrogen storage media, transporting and storing them, and then producing hydrogen on-site through chemical reactions is an effective solution. Ammonia has the advantages of high hydrogen storage capacity (17.6wt%), easy liquefaction (can be liquefied at room temperature and 10 atmospheres), high lower explosion limit, and has a complete production, transportation and storage infrastructure. Therefore, it is considered to be a very promising hydrogen storage material (Ind. Eng.Chem. Res. 2023, 62, 11305-11336).
[0003] In order to realize the on-site production of hydrogen by decomposing ammonia, it is essential to develop efficient and low-temperature catalysts. The metal elements commonly used in ammonia decomposition catalysts include Ru, Rh, Fe, Co, Ni, etc. Among them, the noble metal Ru has the best low-temperature catalytic performance, but its high price limits its large-scale application. In recent years, single-atom catalysts have attracted much attention in the field of catalysis due to their very high catalytic activity and high atomic utilization. Therefore, when preparing ammonia decomposition catalysts, loading active metals (especially noble metal elements such as Ru) on catalyst carriers in the form of single atoms or single-atom clusters can greatly improve the dispersibility and atomic utilization of the active components of the catalyst, thereby reducing the loading amount of active metals without affecting the performance of the catalyst and reducing costs. Researchers have done a lot of work on the design and development of single-atom catalysts, and many preparation methods have been reported. However, since single-atom catalysts usually require relatively sophisticated experimental synthesis methods, this is generally not conducive to large-scale production applications. In addition, the commonly used liquid phase synthesis method uses a large amount of solvents, resulting in problems such as increased costs and environmental pollution. The ball milling method has broad application prospects in the preparation of single atoms in the field of heterogeneous catalysis due to its advantages such as simple process, environmental friendliness and large preparation volume (Materials Today, 2023, 63: 288-312). Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a preparation process for synthesizing a single-atom ammonia decomposition catalyst by mechanical ball milling. Specifically, a mixed material of layered material hexagonal boron nitride and cerium acetylacetonate is used as a precursor of a composite carrier, and the two are pre-mixed, and then the corresponding acetylacetonate salt of the active metal (such as ruthenium acetylacetonate, nickel acetylacetonate) is added as a precursor of the active component, and ball milling is performed after weighing according to a certain mass ratio, and then heat treatment is performed to load the active component onto the carrier to obtain the corresponding ammonia decomposition catalyst. Under the full effect of ball milling, active metals such as ruthenium acetylacetonate and nickel acetylacetonate can be effectively dispersed in the carrier without aggregation, and can be converted into a single-atom form and loaded onto the carrier after high-temperature treatment, so as to realize the preparation of a large-scale ammonia decomposition catalyst. In addition, since the active metal and the carrier are precursors with the same ligand, according to the principle of like dissolves like, the two can be better dispersed with each other, which is more conducive to the uniform loading of active metals such as ruthenium and nickel on the carrier. Moreover, hexagonal boron nitride, which has a layered structure, can be continuously peeled off under the action of ball milling, greatly increasing the specific surface area and defects, and can better adsorb and fix active metals and reduce agglomeration problems.
[0005] The present invention adopts the following technical solution:
[0006] A large-scale preparation method of a single-atom ammonia decomposition catalyst comprises the following steps:
[0007] (1) mixing the layered structure material with a hydrogen peroxide solution, heating for reaction, washing, and drying to obtain a layered structure material modified with a negatively charged hydroxyl functional group;
[0008] (2) mixing a layered structure material modified with a negatively charged hydroxyl functional group and acetylacetonate by ball milling to obtain a precursor of a composite carrier;
[0009] (3) using a metal salt of acetylacetonate corresponding to an active metal as an active component precursor, mixing the active component precursor with a precursor of the composite support, and then continuing ball milling to obtain a ball milled mixture;
[0010] (4) calcining the ball-milled mixture to obtain an ammonia decomposition hydrogen production catalyst in which active metal atoms are dispersed on a hexagonal boron nitride and cerium oxide composite support.
[0011] Furthermore, in step (1), the layered structure material is one or more of hexagonal boron nitride, graphene, graphitic carbon nitride, transition metal sulfide (such as MoSe2 or MoS2) and transition metal oxide; the ratio of the mass of the layered structure material to the volume of the hydrogen peroxide solution is 1:50~100g / ml, and the mass percentage of the hydrogen peroxide solution is 20~40wt% (for example, 20wt%, 30wt% or 40wt%); the heating reaction temperature is 100~150℃ (for example, 100℃, 110℃, 120℃, 130℃, 140℃ or 150℃), and the heating reaction time is 18~48 hours.
[0012] Furthermore, in step (2), the molar ratio of boron nitride to acetylacetonate is 1:1 to 8 (for example, 1:1, 1:3, 1:4, 1:6 or 1:8).
[0013] Furthermore, in step (2), the acetylacetonate in the composite carrier is cerium acetylacetonate, aluminum acetylacetonate or barium acetylacetonate; or the acetylacetonate in the composite carrier is replaced by cerium acetate or aluminum acetate.
[0014] Furthermore, in step (2), the rotation speed used for ball milling pretreatment of the composite carrier precursor is 300-500 r / min and the ball milling time is 4-6 h; in step (3), the rotation speed after adding the active component precursor is 400-800 r / min and the ball milling time is 8-12 h.
[0015] Furthermore, in step (3), the active metal is a precious metal and / or a non-precious metal; the precious metal is one or more of gold, silver, ruthenium, rhodium, palladium, osmium and iridium; the non-precious metal is one or more of nickel, iron and cobalt.
[0016] Furthermore, in step (3), the active metal precursor is one or two of nickel acetylacetonate, ruthenium acetylacetonate, iron acetylacetonate, nickel acetate, ruthenium acetate, iron acetate and cobalt acetylacetonate.
[0017] Furthermore, in step (4), the active component loading amount of the ammonia decomposition catalyst is 1%-5% of the mass of the catalyst for a catalyst whose active metal is a precious metal; and is 10%-60% (e.g., 10%, 20%, 30%, 40% or 60%) of the mass of the catalyst for a catalyst whose active metal is a non-precious metal. Preferably, the catalyst needs to be subjected to reduction pretreatment before use, and the reduction pretreatment conditions are: in a hydrogen-containing mixed gas (e.g., the hydrogen-containing mixed gas is a H2 / Ar mixed gas), the temperature is increased at a rate of 1-8°C / min to 300-500°C for 8-24h.
[0018] Furthermore, in step (4), the calcination temperature is 400-850°C and the calcination time is 3-6h.
[0019] Furthermore, the catalyst prepared by any of the preparation methods described above is used in the production of hydrogen by decomposing ammonia.
[0020] Beneficial effects:
[0021] Hexagonal boron nitride and cerium acetylacetonate, which are layered structures, are used as precursors of composite carriers, and acetylacetonate metal salts with the same ligands are used as active metal precursors. A simple and easy-to-operate ball milling method is used for atomic-level dispersion treatment to achieve the preparation of large-scale ammonia decomposition hydrogen production catalysts. On the one hand, the layered hexagonal boron nitride can be further peeled off under the action of ball milling, exposing a larger specific surface area and defects, which is conducive to the adsorption and fixation of active metals. On the other hand, the addition of cerium acetylacetonate as a composite carrier precursor has the same ligand structure as the active metal precursor acetylacetonate metal salt. According to the principle of similar dissolves, it is more conducive to the mutual dispersion of active metals and carriers, fully improving the dispersibility and uniformity of active metals, and realizing the preparation of atomic-level catalysts. In addition, the preparation process can be carried out directly in the ambient atmosphere, without the need for a protective atmosphere, and is easier to operate, which is conducive to the preparation of large-scale ammonia decomposition hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the preparation of nickel-based ammonia decomposition catalyst with boron nitride and cerium oxide as composite carrier by ball milling. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0024] like Figure 1 As shown, the nickel-based ammonia decomposition catalyst with boron nitride and cerium oxide as a composite carrier is prepared by ball milling, including: nickel acetylacetonate is a precursor of active metal nickel, cerium acetylacetonate and hexagonal boron nitride are precursors of the composite carrier, wherein the hexagonal boron nitride is a layered structure, which can be peeled off to obtain a two-dimensional sheet structure under the action of ball milling, further increasing the specific surface area and defects, and can adsorb and fix more active substances. And under the action of mechanical ball milling, nickel acetylacetonate and cerium acetylacetonate can be dispersed at the atomic level, and loaded and fixed on the two-dimensional sheet-like hexagonal boron nitride, and then calcined to obtain a nickel-based ammonia decomposition catalyst with boron nitride and cerium oxide as a composite carrier.
[0025] Example 1
[0026] A large-scale preparation method of a single-atom ammonia decomposition catalyst comprises the following steps:
[0027] 1) Pretreatment of carrier:
[0028] Before use, h-BN (hexagonal BN; Tianyuan Aerospace Materials, item number: H-BN-C) needs to be treated. Specifically, 1g of h-BN is dispersed in 70ml of 30% hydrogen peroxide solvent and stirred magnetically for 24h. Then it is transferred to an autoclave with a polytetrafluoroethylene liner and reacted at 120℃ for 24h to achieve the purpose of modifying the surface of boron nitride with negatively charged hydroxyl functional groups. After the reaction, the boron nitride is washed with deionized water three times and centrifuged, and dried at 80℃ for 12h for use. According to the molar ratio of 1:4, a certain mass of surface-modified h-BN and cerium acetylacetonate (Ce(acac)3) are weighed respectively, placed in an agate ball mill, and 50 ball mills with a diameter of 3mm are added. The ball mill is fixed on the base of the ball mill to ensure that it will not fall off and move during operation. The ball milling treatment was carried out at a rotation speed of 500 r / min for 4 hours to obtain a BN-Ce(acac)3 mixture, i.e., a precursor of the BN-CeO2 composite carrier.
[0029] 2) Ball milling of active metal and carrier mixture
[0030] According to the doping ratio of active metals (based on the total mass of the atomically dispersed nickel-based ammonia decomposition catalyst prepared in step 3, where the Ni loading is 10wt%), a certain amount of nickel acetylacetonate (Ni(acac)2) and BN-Ce(acac)3 mixture is weighed and placed in a 100ml ball mill (agate ball mill is used, and 50 ball mill beads with a diameter of 3mm are added). After fixing the ball mill to the base, start the machine in the ambient atmosphere, set the speed to 800r / min, and the running time is 8h. The planetary ball mill used can accommodate four ball mills running at the same time, so it can realize the preparation of multiple cans of catalyst at one time, greatly improving the synthesis efficiency.
[0031] 3) High temperature treatment to obtain Ni / BN-CeO2 ammonia decomposition hydrogen production catalyst
[0032] After the ball milling is completed, the ball milling beads are separated from the powder, and the powder material is calcined in air at 850°C for 3 hours to finally obtain an atomically dispersed nickel-based ammonia decomposition catalyst with BN and CeO2 as a composite carrier (based on the total mass of the atomically dispersed nickel-based ammonia decomposition catalyst, the Ni loading is 10wt%). Since the calcination is in the air, the active metal is dispersed on the carrier in the form of the corresponding oxide, so the catalyst needs to be reduced and pretreated before use.
[0033] 4) Performance test of ammonia decomposition catalyst
[0034] Take 1.5 g of ammonia decomposition catalyst and load it into a fixed bed reactor. Before testing, the reactor should be heated at a flow rate of 30 mL min (based on the total volume of the mixed gas). -1 The samples were pretreated in a H2 / Ar mixed gas (the H2 content was 10% based on the total volume of the mixed gas) for 12 h (temperature was 400°C, heating rate was 5°C / min). The gas was then switched to ammonia and the ammonia decomposition rate was tested at 500°C, 550°C, 600°C, 650°C, and 700°C with a flow rate of 83.5 ml min -1 , space velocity is 10020 mL g -1 h -1 The ammonia conversion rate can be calculated by the formula: Ammonia conversion rate = (initial ammonia content - tail gas ammonia content) / initial ammonia content × 100%.
[0035] Optionally, in step (2), the corresponding acetylacetonate metal salt is selected as the active metal precursor, including but not limited to Ru(acac)3, Rh(acac)3, Ni(acac)3, Fe(acac)3, Co(acac)3, etc. to replace Ni(acac)2, and the carrier in step (1) can also be one or two or more of Ce(acac)3, Al(acac)3, Ba(acac)2▪xH2O, hexagonal boron nitride, carbonitride, etc. In step (2), the speed setting of the ball milling process can be forward 400-800r / min or reverse 400-800r / min, and there is no need to alternate forward and reverse operation.
Claims
1. A large-scale preparation method of a single-atom ammonia decomposition catalyst, characterized in that: The following steps are involved: (1) mixing the layered structure material with a hydrogen peroxide solution, heating for reaction, washing, and drying to obtain a layered structure material modified with a negatively charged hydroxyl functional group; (2) mixing a layered structure material modified with a negatively charged hydroxyl functional group and acetylacetonate by ball milling to obtain a precursor of a composite carrier; (3) using a metal salt of acetylacetonate corresponding to an active metal as an active component precursor, mixing the active component precursor with a precursor of the composite support, and then continuing ball milling to obtain a ball milled mixture; (4) calcining the ball-milled mixture to obtain an ammonia decomposition hydrogen production catalyst in which active metal atoms are dispersed on a hexagonal boron nitride and cerium oxide composite support.
2. The preparation method according to claim 1, characterized in that: In step (1), the layered structure material is one or more of hexagonal boron nitride, graphene, graphitic carbon nitride, transition metal sulfide (such as MoSe2 or MoS2) and transition metal oxide; the ratio of the mass of the layered structure material to the volume of the hydrogen peroxide solution is 1:50~100g / ml, and the mass percentage of the hydrogen peroxide solution is 20~40wt%; the heating reaction temperature is 100~150°C, and the heating reaction time is 18~48 hours.
3. The preparation method according to claim 1, characterized in that: In step (2), the molar ratio of boron nitride to acetylacetonate is 1:1-8.
4. The preparation method according to claim 1, characterized in that: In step (2), the acetylacetonate in the composite carrier is cerium acetylacetonate, aluminum acetylacetonate or barium acetylacetonate; or the acetylacetonate in the composite carrier is replaced by cerium acetate or aluminum acetate.
5. The preparation method according to claim 1, characterized in that: In step (2), the composite carrier precursor is pre-milled at a rotation speed of 300-500 r / min and a ball milling time of 4-6 h. In step (3), the rotation speed after adding the active component precursor is 400-800 r / min and the ball milling time is 8-12 h.
6. The preparation method according to claim 1, characterized in that: In step (3), the active metal is a precious metal and / or a non-precious metal; the precious metal is one or more of gold, silver, ruthenium, rhodium, palladium, osmium and iridium; the non-precious metal is one or more of nickel, iron and cobalt.
7. The preparation method according to claim 1, characterized in that: In step (3), the active metal precursor is one or two of nickel acetylacetonate, ruthenium acetylacetonate, iron acetylacetonate, nickel acetate, ruthenium acetate, iron acetate and cobalt acetylacetonate.
8. The preparation method according to claim 1, characterized in that: In step (4), the active component loading amount of the ammonia decomposition catalyst is 1%-5% of the catalyst mass for a catalyst whose active metal is a precious metal; and 10%-60% of the catalyst mass for a catalyst whose active metal is a non-precious metal. Preferably, the catalyst needs to be subjected to reduction pretreatment before use, and the reduction pretreatment conditions are: in a hydrogen-containing mixed gas (for example, the hydrogen-containing mixed gas is a H2 / Ar mixed gas), the temperature is increased at a rate of 1-8°C / min to 300-500°C for 8-24h.
9. The preparation method according to claim 1, characterized in that: In step (4), the calcination temperature is 400-850°C and the calcination time is 3-6 hours.
10. Use of the catalyst prepared by the preparation method according to any one of claims 1 to 9 in the production of hydrogen by decomposing ammonia.